Arsenic trioxide inhibits liver cancer stem cells and metastasis by targeting SRF/MCM7 complex - Wang, Hai-Yang (Cell Death Dis, 2019)
Hepatocellular carcinoma (HCC) has a high mortality rate due to the lack of effective treatments and drugs. Arsenic trioxide (ATO), which has been proved to successfully treat acute promyelocytic leukemia (APL), was recently reported to show therapeutic potential in solid tumors including HCC. However, its anticancer mechanisms in HCC still need further investigation. In this study, we demonstrated that ATO inhibits tumorigenesis and distant metastasis in mouse models, corresponding with a prolonged mice survival time. Also, ATO was found to significantly decrease the cancer stem cell (CSC)-associated traits. Minichromosome maintenance protein (MCM) 7 was further identified to be a potential target suppressed dramatically by ATO, of which protein expression is increased in patients and significantly correlated with tumor size, cellular differentiation, portal venous emboli, and poor patient survival. Moreover, MCM7 knockdown recapitulates the effects of ATO on CSCs and metastasis, while ectopic expression of MCM7 abolishes them. Mechanistically, our results suggested that ATO suppresses MCM7 transcription by targeting serum response factor (SRF)/MCM7 complex, which functions as an important transcriptional regulator modulating MCM7 expression. Taken together, our findings highlight the importance of ATO in the treatment of solid tumors. The identification of SRF/MCM7 complex as a target of ATO provides new insights into ATO’s mechanism, which may benefit the appropriate use of this agent in the treatment of HCC.